Data curation in the Internet of Things: A decision model approach. Issue 6 (28th September 2021) - de Haro‐Olmo, Francisco José; Valencia‐Parra, Álvaro; Varela‐Vaca, Ángel Jesús; Álvarez‐Bermejo, José Antonio
Abstract: Current Internet of Things (IoT) scenarios have to deal with many challenges especially when a large amount of heterogeneous data sources are integrated, that is, data curation. In this respect, the use of poor‐quality data (i.e., data with problems) can produce terrible consequence from incorrect decision‐making to damaging the performance in the operations. Therefore, using data with an acceptable level of usability has become essential to achieve success. In this article, we propose an IoT‐big data pipeline architecture that enables data acquisition and data curation in any IoT context. We have customized the pipeline by including the DMN4DQ approach to enable us the measuring and evaluating data quality in the data produced by IoT sensors. Further, we have chosen a real dataset from sensors in an agricultural IoT context and we have defined a decision model to enable us the automatic measuring and assessing of the data quality with regard to the usability of the data in the context.